The Organic Codes: An Introduction to Semantic Biology. - Markoš, Anton; Gajdoš, Eduard; Hajnal, László; Cvrčková, Fatima (Sign Systems Studies, 2003)
The article reviews the book "The Organic Codes: An Introduction to Semantic Biology," by Marcello Barbieri.